Self-reported lower gastrointestinal endoscopy use and changes in colorectal cancer mortality rates in European countries - Chen, Chen; Stock, Christian; Hoffmeister, Michael; Brenner, Hermann (Clinical and translational gastroenterology, 2020)
INTRODUCTION: - To quantify the association of self-reported lower gastrointestinal endoscopy use measured in 2004/05 with colorectal cancer (CRC) mortality changes over 2004-2015 in Europe. - METHODS: - An ecological analysis was performed using endoscopy utilization data from the Survey of Health, Aging, and Retirement in 11 European countries in 2004/05 and CRC mortality data from the World Health Organization Mortality Database over 2004-2015. Mortality trends were compared through annual mortality changes from joinpoint regression models. Cross-national variations in mortality trends with respect to endoscopy use were tested for statistical significance by negative binomial regression models. - RESULTS: - The proportion of respondents who reported having had an endoscopy within 10 years varied widely across countries, from 6.1% to 25.1%. Large disparities in CRC mortality trends were also observed, with annual mortality change ranging from a decline of 3.3% to an increase of 0.9% for men and from a decline of 3.3% to a decline of 0.6% for women. Endoscopy uptake was negatively associated with the magnitude of annual mortality change over 2004-2015 (rate ratio for a 10-year mortality change per 10% higher endoscopy use, 0.88; 95% confidence interval, 0.82-0.94). - DISCUSSION: - This analysis provides quantitative evidence on the contributions of endoscopy use to CRC mortality declines in European countries over the past decade. A considerable fraction of protection is likely to be delivered through endoscopic removal of adenomas and sessile serrated lesions. With many European countries having recently implemented CRC screening programs, an increase in endoscopy use and a subsequent reduction in CRC mortality would be expected.
Published online October 6, 2020
Gesehen am 30.09.2021